STRATEGIES FOR ENHANCING THE PERFORMANCE OF LI [NIXCOYMN1-X-Y] O2 CATHODE MATERIALS FOR LI-ION BATTERIES - YOLA BERTILSYA HENDRI; Heni Sugesti; Zuqni Meldha; Lisa Legawati; Salma Liska; Yogi Yolanda; Amun Amri (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
Abstract Li[NixCoyMn1-x-y]O2 layered oxides Cathode Materials are among the most widely studied cathode materials for lithium-ion batteries due to their high gravimetric and volumetric energy density compared to other type cathode materials. However, the practical deployment of Ni-rich NCM materials is hindered by severe degradation mechanisms, including cation-mixing, surface reconstruction, electrolyte reactivity, transition metal dissolution, and oxygen release, which compromise cycling stability and safety. This review systematically synthesizes recent progress in advanced modification strategies designed to mitigate degradation in Li[NixCoyMn1-x-y]O2 cathodes. The discussion is structured into four major approaches: (i) surface modification, which employs protective coatings to suppress interfacial reactions and stabilize the cathode–electrolyte interphase; (ii) elemental doping, which strengthens the lattice, reduces cation mixing, and inhibits oxygen evolution; (iii) single-crystal engineering, which eliminates grain-boundary failure and improves thermal stability; and (iv) concentration-gradient architectures, which alleviate internal stress and enhance the durability of Ni-rich cathodes. Empirical evidence demonstrates that these strategies not only extend cycle life but also provide mechanistic insights into the underlying degradation pathways. By consolidating findings from recent experimental, this review highlights the necessity of integrating structural, chemical, and morphological interventions to realize the full potential of Ni-rich NCM cathodes. The insights presented offer a framework for designing safer, higher-performance, and commercially scalable lithium-ion batteries. Abstrak Li[NixCoyMn1-x-y]O2 berbasis oksida berlapis merupakan salah satu material katoda yang paling banyak dikaji dalam pengembangan baterai litium-ion. Keunggulan utamanya terletak pada kerapatan energi gravimetri dan volumetri yang lebih tinggi dibandingkan dengan jenis katoda lain. Namun demikian, penerapan praktis material NCM kaya nikel masih menghadapi sejumlah kendala serius akibat berbagai mekanisme degradasi, antara lain pencampuran kation, rekonstruksi permukaan, reaktivitas dengan elektrolit, pelarutan logam transisi, serta pelepasan oksigen. Mekanisme-mekanisme tersebut secara langsung menurunkan stabilitas siklus dan tingkat keselamatan baterai.Ulasan ini menyajikan sintesis sistematis mengenai perkembangan mutakhir strategi modifikasi lanjutan yang dirancang untuk menekan degradasi pada katoda Li[NixCoyMn1-x-y]O2. Terdapat empat pendekatan utama yang dibahas, yaitu: (i) modifikasi permukaan, melalui penerapan lapisan pelindung guna menekan reaksi antarmuka dan menstabilkan lapisan katoda–elektrolit; (ii) doping unsur, yang berfungsi memperkuat struktur kisi, mengurangi pencampuran kation, serta menekan evolusi oksigen; (iii) rekayasa kristal tunggal, yang mengatasi kegagalan pada batas butir sekaligus meningkatkan stabilitas termal; dan (iv) arsitektur gradien konsentrasi, yang mampu meredam tegangan internal dan memperpanjang daya tahan katoda kaya nikel. Hasil-hasil empiris menunjukkan bahwa penerapan strategi tersebut tidak hanya memperpanjang umur pakai siklus, tetapi juga memperkaya pemahaman tentang mekanisme degradasi yang mendasari. Dengan mengintegrasikan temuan-temuan eksperimental terbaru, ulasan ini menegaskan pentingnya perpaduan intervensi struktural, kimia, dan morfologis untuk mengoptimalkan kinerja katoda NCM kaya nikel. Wawasan yang dihadirkan sekaligus menawarkan kerangka konseptual bagi pengembangan baterai litium-ion yang lebih aman, berkapasitas tinggi, dan memiliki prospek komersialisasi yang luas.